a) b) c) d)
1) Examining each function, let's test considering that the average rate of change is given by:
![\Delta=(f(b)-f(a))/(b-a)](https://img.qammunity.org/2023/formulas/mathematics/college/flcfup8lj4y3c58nhefakg5zmotgmij9zt.png)
2) So let's plug the functions:
![\begin{gathered} a)\text{ }\Delta=\frac{(100)+2\text{ -\lbrack(0)+2\rbrack}}{100-0}=(102-2)/(100)=(100)/(100)=1 \\ b)\text{ }g(x)=2^x\text{ }\Delta=(2^(100)-2^0)/(100-0)=(1.26*10^(30))/(100)=1.26*10^(28) \\ c)\text{ }h(x)\text{ = }111x-23\text{ }\Delta=\frac{111(100)-23\text{ -\lbrack{}111(0)-23}}{100}=111 \\ d)\text{ }p(x)\text{ = }50,000*3^x\Delta=(50,000-3^(100)-\lbrack50,000-3^0)/(100)=-5.15*10^(45) \\ e)q(x)=87.5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bmqvzu112cu1x3aps1numicsmiiurbwl31.png)
3) Since the average rate of change is a "measure of how much a function changes in the given interval" and considering that we have linear and exponential functions and the last one e) is not a function but an equation.
Then we can say that for the functions below the average rate of change is a good measure, not applying for the last one which, indeed is not a function.
a)
b)
c)
d)